Expression and significance of survivin in colorectal high grade and low grade adenomas - Adamkov, Marian; Výbohová, Desanka; Tupá, Veronika; Chylíková, Jaroslava; Horáček, Jaroslav; Benčat, Marián (Acta histochemica, 2015)
We examined immunohistochemically the expression pattern of a potential tumor biomarker survivin in a panel of 116 tubular adenomatous polyps to determine its association with clinicomorphological parameters such as age of patients, size of polyps, degree of dysplasia and polyp localization. In each section, the subcellular localization of survivin antigen and the intensity of staining were assessed. Overall, survivin was expressed in 90 cases (77.6%). Cytoplasmic positivity was observed in 46/116 cases (39.7%), while nuclear and combined nuclear and cytoplasmic reaction in 44/116 cases (37.9%). High grade dysplasia was diagnosed in 52 cases (44.8%) and low grade dysplasia in 64 cases (55.2%). Statistical analysis revealed a significant correlation between subcellular survivin localization and the degree of dysplasia, size of polyps and colon localization. On the other hand, survivin expression pattern did not correlate with the age of patients. Statistically significant trend was confirmed between intensity of survivin immunoreaction and tumor size and dysplasia grade, and also the trend between negative/strong survivin intensity and polyp localization. Another statistically significant association was found between the degree of dysplasia and the size of polyps. Our findings revealed that survivin is frequently expressed in different subcellular compartments of adenoma cells. Our recent results suggest that the nuclear and combined nuclear and cytoplasmic survivin localizations are strongly associated with poor prognostic parameters in the assessment of colon adenomas. Thus, survivin may represent a promising biomarker in immunohistochemical evaluation of these lesions.
Keywords: senioři; Biomarker; survivin; Tubular adenoma; Survivin; Prognosis; imunohistochemie; Middle Aged; mužské pohlaví; adenom; Adenoma; Biomarkers, Tumor; Colon; nádory tračníku; Immunohistochemistry; inhibitory apoptózy; ženské pohlaví; nádorové biomarkery; prognóza; Humans; kolon; Colonic Neoplasms; lidé středního věku; Female; Aged; Inhibitor of Apoptosis Proteins; lidé; Male